The Influence of the Intelligence Mapping Presentation Learning Model on the Learning Interest of Fourth Grade Students at SD Negeri 0105 Sibuhuan - Rani Astria Silvera Harahap; Rifati Suhaila Siregar; Nurhayati Siregar (PT. Gyandharma Global Media, 2026)
The purpose of this research is to find out: (1) how interested in learning grade IV students at SD Negeri 0105 Sibuhuan are. (2) what is the influence of the intelligence mapping presentation learning model on the learning interest of class IV students at SD Negeri 0105 Sibuhuan. The type of research used by researchers is the experimental method. The essence of experimental research. The data collection techniques used are questionnaires, tests and documentation. The sample in this study was 36 students consisting of 18 students from class IV-A experimental class and 18 students from class IV-B control class with data analysis techniques using normality tests, homogeneity tests and hypothesis tests. Based on the results of the research carried out by the researcher, it can be concluded that (1) The interest in learning of class IV students at SD Negeri 0105 Sibuhuan at the pre-test stage obtained an average of 48.72 in the experimental class and the average post-test score. experimental class test was 80.83. Meanwhile, the average pre-test result for the control class was 43.16 and the average post-test result for the control class was 49.94. Thus the average of the experimental class is higher than the control class. (2) Test the hypothesis using the T test and the calculation results show that the Tcount value is 2.03 when compared with Ttable at a significance level of 5% or 0.05 with degrees of freedom (dk) = 16 which is 1.74. Based on these data, Tcount is greater than Ttable or (2.03 > 1.74), so Ha is accepted and Ho is rejected. So it can be concluded that there is a significant influence of the intelligence mapping presentation learning model on the learning interest of class IV students at SD Negeri 0105 Sibuhuan. This is an open access article under the CC–BY-SA